2020
DOI: 10.1136/archdischild-2019-317932
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and aetiology of cerebral palsy in children from Cross River State, Nigeria

Abstract: ObjectiveThere are few studies on cerebral palsy (CP) in African children and our study aimed to describe the aetiology, characteristics and severity of CP in children from Nigeria.DesignA population-based study using key informant methodology (KIM) was conducted as part of a clinical research trial. Children aged 4–15 years were clinically assessed for CP.ResultsThe estimated prevalence of CP using KIM was 2.3/1000 children (95% CI 2.0 to 2.5/1000). 388 children were diagnosed with CP, with Gross Motor Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 28 publications
2
31
2
Order By: Relevance
“…The 2020 population-based study from Nigeria indicated 36% postneonatal risk factors in their cohort, with malaria with seizures accounting for 72% of the cases. [27] Post-neonatal complications were identified in 17% of our study participants, which was similar to the findings from Benin (17%) and Uganda (18%). [25,26] Malaria and seizures contributed to the post-neonatal complications in both these countries.…”
Section: Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…The 2020 population-based study from Nigeria indicated 36% postneonatal risk factors in their cohort, with malaria with seizures accounting for 72% of the cases. [27] Post-neonatal complications were identified in 17% of our study participants, which was similar to the findings from Benin (17%) and Uganda (18%). [25,26] Malaria and seizures contributed to the post-neonatal complications in both these countries.…”
Section: Researchsupporting
confidence: 88%
“…[25,26] A recent population-based study on the clinical features and aetiology of CP in Nigeria published in 2020, reported premature birth in 8% of their cohort. [27] Although the present analysis indicated a higher rate of prematurity (31%), it is less in comparison with the Pan-European cohort reported by Horber et al [19] (41%) and the systematic review by Franki et al (44%). [11] The higher proportion of PGMI in our cohort as well as elsewhere in Africa is probably related to the poor survival of premature infants in Africa, as well as the relative underrepresentation of premature infants in our cohort.…”
Section: Researchcontrasting
confidence: 76%
“…The numbers for postneonatal CP in HICs are small, and we have less confidence about these trends, particularly for children with a brain injury closer to the age of 2 years, which may be described as an acquired brain injury rather than postneonatal CP. LMICs with higher proportions of postneonatal CP (up to 36% in Nigeria, 36 compared with 6% in Australia 2 ), alert us to the differences in aetiologies of postneonatal CP (e.g. malaria, previous nutritional status) and potentially different opportunities for prevention strategies that are specific to each region 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Preventable postnatal risk factors for CP are more prevalent in LMICs than HICs and include bacterial meningitis, meningoencephalitis and cerebral malaria [3,[59][60][61]. In a population-based study in Uganda, cerebral injury resulting in CP was attributed to cerebral malaria/cerebral infections in 25% of cases [60].…”
Section: Meningitis/meningoencephalitis Cerebral Malaria and Cpmentioning
confidence: 99%